EMPLOYER BRANDING IN PRACTICE : FOSTERING JOB SATISFACTION AND SUSTAINING EMPLOYEE RETENTION IN THE PALM OIL INDUSTRY - Sabeli Aliya; Putri Yulianti (Universitas Nusa Cendana, 2026)
The highly competitive nature of the palm oil industry requires companies to implement strategic human resource management practices, with employer branding playing a crucial role in enhancing organizational competitiveness. This study investigates the effect of employer branding on employee retention, with job satisfaction acting as a mediating variable, at PT Surya Alam Permai. A quantitative research approach was employed using purposive sampling, involving 50 respondents selected from a total population of 150 employees. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the relationships among the research variables. The findings reveal that employer branding has a positive and significant effect on job satisfaction. Furthermore, employer branding directly enhances employee retention. Job satisfaction also exerts a positive and significant influence on employee retention. In addition, job satisfaction significantly mediates the relationship between employer branding and employee retention, indicating that a strong employer image increases retention both directly and indirectly through enhanced employee satisfaction. These results underscore the strategic importance of employer branding in fostering job satisfaction, strengthening employee loyalty, and reducing turnover rates. Ultimately, an effective employer branding strategy contributes to long-term organizational sustainability and competitive advantage. Keywords: Employer Branding; Employee Retention; Job Satisfaction; Palm Oil Plantation; Processing Industry